O Papa é pop : o primeiro pontífice latino-americano como centro das atenções - Maíra Lobato Bicalho Chagas Moura Campos (2017)
The Catholic Church has elected, in 2013, the first non-European pontiff of the history of Catholicism. The Argentinian Cardinal Jorge Mario Bergoglio became Pope after the conclave, held in March of that year, and adopted the name “Francis”. The new Catholic leader brought great expectations about his stance as pontiff. With the attitude of a simple man and showing great concern about human relationships, Bergoglio became the center of attentions worldwide. This work is a reflection on the role of celebrity occupied by Pope Francis through the analysis of news published on the site G1 during the pontificate’s first year. For this, we analyse the biography of Bergoglio, the context of the Catholic Church, and we use the concept of celebrity and reflections of different authors on contemporary society. The concept of celebrity shows itself very useful for understanding the various operations of construction of meaning around a public figure. Once celebrities are understood as figures that attract different levels of adhesion between people and are from different contexts, this concept allows us to reflect on the traits that stand in relation to these figures, revealing values that circulate in our society. The news articles were grouped into categories by means of a content analysis. This first group had the aim to organize the material collected and enable the analysis in seven other groups related to the concept of celebrity: attributes and personal characteristics of a celebrity; the social position occupied by it; the media visibility; the context in which a celebrity emerges; the table of values; the interaction with the public and the themes that circulate around it. It was then possible to observe distinct features of our society revealed by the figure of Pope Francis.